2016
DOI: 10.1590/s1677-5538.ibju.2015.0741
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of cystine and struvite stone formers: clinical, metabolic and surgical assessment

Abstract: Purpose:To compare the clinical, metabolic, and calculi characteristics of cystine and struvite stone patients after percutaneous nephrolithotripsy (PCNL).Material and Methods:Between January/2006-July/2013, 11 cystine stone patients were treated in our clinic. Of those, 3 were excluded due to incomplete follow-up. Eight cystine stone patients (2 with bilateral disease; 10 renal units-RU) were considered for further analysis. A cohort of 8 struvite stone formers (10RU) was matched having the same age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…10, 11, 17-20, 23-34 20 studies reported outcomes from surgical interventions in cystinuria patients. 10, 11, 17-20, 24-26, 29, 30, 32-40 Of the 24 studies, 15 reported combined intervention methods with alkalinizing compounds, pharmacological drugs and/or surgical procedures. 10, 11, 17-20, 24-27, 29, 30, 32-34 No studies directly compared pharmacological intervention to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…10, 11, 17-20, 23-34 20 studies reported outcomes from surgical interventions in cystinuria patients. 10, 11, 17-20, 24-26, 29, 30, 32-40 Of the 24 studies, 15 reported combined intervention methods with alkalinizing compounds, pharmacological drugs and/or surgical procedures. 10, 11, 17-20, 24-27, 29, 30, 32-34 No studies directly compared pharmacological intervention to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
“…19 studies reported mean patient age, which ranged from 7.4 to 49 years. 10, 17-20, 23-28, 31, 32, 34-38, 40 Of the 24 studies, 5 reported median patient age, which ranged from 6 to 18.5 years. 11, 29, 30, 33, 39…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite constituting only 1% of adult and 6–10% of paediatric urinary tract calculi [ 1 3 ], patients with cystinuria are often the most challenging stone formers to manage [ 4 , 5 ]. With initial stone presentation often within the first two decades of life and recurrence rates of 60% or greater [ 6 ], cystinurics require lifelong treatment and intensive follow-up.…”
Section: Introductionmentioning
confidence: 99%